A Comparative Analysis of Cultural Terms in Arabic-Javanese Religious Texts Through the Lens of al-Hikam Aphorisms Translation - Anis, Muhammad Yunus; Syed Abdullah, Syed Nurulakla bin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Local wisdom stood as a cornerstone of Indonesia's cultural richness. Regrettably, this invaluable asset, particularly in the form of "translation products," was overlooked and underappreciated. Despite Indonesia boasting a substantial collection of Arabic religious texts translated into Javanese, utilizing the pegon script, these Arabic-Javanese texts demanded preservation, scholarly exploration, and development grounded in specific theoretical frameworks. This research undertook a comparative analysis of "cultural terms" within religious texts, focusing on al-Hikam aphorisms translated from Arabic (L1) into both Indonesian and Javanese (L2). The primary objective was to dissect and analyze the local wisdom and Islamic Sufism moral values embedded in al-Hikam aphorisms through translation. The study drew on translations of words, phrases, clauses, and sentences from carefully selected sources related to cultural terms, including books and various Arabic-Javanese translation dictionaries. Employing a purposive sampling method, data collection followed a meticulous process. Qualitative data analysis unfolded through four pivotal stages: (1) domain analysis, (2) taxonomy analysis, (3) componential analysis, and (4) cultural theme analysis. The findings, gleaned from lexicography study and semantic analysis of translation, revealed the existence of two translation ideologies shaping cultural terms in Arabic-Javanese religious texts: domestication ideology and foreignization ideology. This research underscored that translation products were inseparable from the ideological dimensions of foreignization and domestication. Foreignization endeavored to assimilate source language elements into the target language, while domestication integrated original components with local elements. This research contributed to a deeper understanding of how foreignization and domestication shaped the depiction of local wisdom in Arabic-Javanese religious texts.